'The sweet tang of rape': Torture, survival and masculinity in Ian Fleming's Bond novels. (August 2017) - Adams, Alex
Little scholarly attention has been paid to the torture scenes in Ian Fleming's canon of Bond novels and short stories (1953–1966), despite the fact that they represent some of the most potent sites of the negotiations of masculinity, nationhood, violence and the body for which Fleming's texts are critically renowned. This article is an intersectional feminist reading of Fleming's canon, which stresses the interpenetrations of homophobia, anticommunism and misogyny that are present in Fleming's representation of torture. Drawing on close readings of Fleming's novels and theoretical discussions of heteronormativity, homophobia and national identity, this article argues that Fleming's representations of torture are sites of literary meaning in which the boundaries of hegemonic masculinity are policed and reinforced. This policing is achieved, this article argues, through the associations of the perpetration of torture with homosexuality and Communism, and the survival of torture with post-imperial British hegemonic masculinity. Fleming's torture scenes frequently represent set pieces in which Bond must reject or endure the unsolicited intimacy of other men; he must resist their seductions and persuasions and remain ideologically undefiled. Bond's survival of torture is a metonymy for Britain's survival of post-Second World War social and political upheaval. Further, the horror of torture, for Fleming, is the horror of a hierarchy of hegemonic masculinity in disarray: Bond's survival represents the regrounding of normative heterosexual masculinity through the rejection of homosexuality and Communism.